De-Radicalization through Education Reforms: Comparative Analysis of Closed-Book and Open Book Examination Regime - Farhan Akhtar (Journal of Political Studies, 2021)
The education system in Pakistan, especially its closed-book examination regime, is the legacy of the British Raj dating back to 1857. The examination style of the University of London was introduced in the subcontinent for native students at the high school level to promote English and with an incentive of preference in government jobs. Since the creation of Pakistan, the closed-book examination system, instead of evolving with the changing requirements, got further strengthened where it was also introduced in the higher education in the country. A closed-book examination system promotes rote learning and memorization among the students to fetch good grades. The entire purpose of education becomes questionable when student's efficacy and intellect are assessed in the light of marks attained. The GAP culture of educational institutions is detrimental to the students and society alike. Education in itself has shrunk to passing the exams for promotion to the next level or attaining jobs rather than developing the personalities and transforming the youth into thinking minds and effective, contributing members of the society. Education in Pakistan is merely a test of memory where those with good memory skills who can reproduce the textbooks as verbatim attain good marks and are considered educated and knowledgeable, and failures are discarded from the society. Closed-book examinations are at a tangent to critical, reflective, and creative thinking skills. The analytical abilities of the students of this exam regime are at its lowest ebb. In order to address the menace of extremism, violence, increasing intolerance, and exclusivity in the society, there is a need to find an alternate in the shape of an open-book examination regime that will promote critical, reflective, and problem-solving skills among the youth. Open-book exams assess the true analytical skills of the students, and since this type of examination can only be attempted by students with conceptual clarity and enhanced understanding instead of parroting and rote learning.